2020
DOI: 10.3389/fimmu.2020.01389
|View full text |Cite
|
Sign up to set email alerts
|

IL33 and Mast Cells—The Key Regulators of Immune Responses in Gastrointestinal Cancers?

Abstract: The Interleukin (IL-)1 family IL33 is best known for eliciting type 2 immune responses by stimulating mast cells (MCs), regulatory T-cells (Tregs), innate lymphoid cells (ILCs) and other immune cells. MCs and IL33 provide critical control of immunological and epithelial homeostasis in the gastrointestinal (GI) tract. Meanwhile, the role of MCs in solid malignancies appears tissue-specific with both pro and anti-tumorigenic activities. Likewise, IL33 signaling significantly shapes immune responses in the tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 144 publications
(168 reference statements)
0
15
0
Order By: Relevance
“…Although it is unknown exactly how autoimmune tissue damage may trigger type 2 inflammation and tumorigenesis, IL33 could be a major player. IL33 is constitutively expressed in epithelial cells, endothelial cells, and fibroblasts and can be induced in hematopoietic cells like mast cells, macrophages, and neutrophils ( Afferni et al, 2018 ; Eissmann et al, 2020 ). Under physiologic conditions, IL33 localizes to the nucleus where it can regulate gene expression by binding to histones or influencing histone deacetylase activity ( Afferni et al, 2018 ; Larsen et al, 2018 ).…”
Section: Il33 Is Triggered By Autoimmune Tissue Damage and Potentially Initiates Type 2 Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is unknown exactly how autoimmune tissue damage may trigger type 2 inflammation and tumorigenesis, IL33 could be a major player. IL33 is constitutively expressed in epithelial cells, endothelial cells, and fibroblasts and can be induced in hematopoietic cells like mast cells, macrophages, and neutrophils ( Afferni et al, 2018 ; Eissmann et al, 2020 ). Under physiologic conditions, IL33 localizes to the nucleus where it can regulate gene expression by binding to histones or influencing histone deacetylase activity ( Afferni et al, 2018 ; Larsen et al, 2018 ).…”
Section: Il33 Is Triggered By Autoimmune Tissue Damage and Potentially Initiates Type 2 Inflammationmentioning
confidence: 99%
“…The ST2 receptor is expressed in most hematopoietic cells, particularly T reg cells, ILC2 cells, and mast cells ( Afferni et al, 2018 ; Figure 3 ). This pathway upregulates type 2 inflammation by skewing naïve CD4 + T cells toward Th2 or CD4 + T helper 9 cell differentiation, triggering ILC2 cells to secrete IL5 and IL13, activating mast cells, and driving M2 polarization of macrophages ( Afferni et al, 2018 ; Eissmann et al, 2020 ).…”
Section: Il33 Is Triggered By Autoimmune Tissue Damage and Potentially Initiates Type 2 Inflammationmentioning
confidence: 99%
“…In addition, among the seven genes contained in SDIS, NDRG2 has been shown to be involved in tumor biological processes such as PI3K/Akt, apoptosis and autophagy [36] . IL33 also plays an integral role in tumor development and immune responses [37] . However, because these genes have shown great clinical predictive in tumors and few existing studies have been reported, the role and related mechanism of these genes in tumors need more studies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two papers demonstrated that IL-33 and ILC2s cooperate to suppress innate type 1 immunity and promote tumor development in lung cancer [20] and multiple myeloma [19]. Furthermore, current strategies used to target TME components also include inhibiting macrophage recruitment and differentiation and targeting CAFs and mast cells, also part of the IL-33-involved immune response [110,111].…”
Section: Targeting the Immune Cells In The Tumor Microenvironmentmentioning
confidence: 99%